Congress Volume Aberdeen 2019 - Macaskill, Grant,; Maier, Christl M.,; Schaper, Joachim, (Vetus Testamentum, Supplements ;, 2022)
This volume presents the main lectures of the 23rd Congress of the International Organization for the Study of the Old Testament (IOSOT) held in Aberdeen, United Kingdom, in August 2019. Twenty internationally distinguished scholars present their current research on the Hebrew Bible, including the literary history of the Hebrew text, its Greek translation, and the history of interpretation. Some focus on the semantic and syntactic features of the biblical text and its impact on cultural memory while others deal with textual witnesses in the Dead Sea scrolls, Ethiopic sources, and Arabic translations. The volume gives readers a representative view of recent research on the Hebrew Bible.